(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Conversion is the process of changing or causing something to change from one form to another. Conversion consists in making a new word from some existing word by changing the category of a part of speech; the morphemic shape of the original word remains unchanged: love — to love, paper — to paper, brief — to brief, work — to work; etc.Today, conversion is widely used by linguists and new language learners and is very common in linguistics.From this article we can learn a lot about conversion through examples such as its origin and also why use conversion?